Public and patient involvement in research to support genome services development in the UK - Hunter, A; Lewis, C; Hill, M; Chitty, LS; Leeson-Beevers, K; McInnes-Dean, H; Harvey, K; Pichini, A; Ormondroyd, E; Thomson, K (OAE Publishing, 2023)
Public and patient involvement (PPI) - the collaboration in research with members of the public and patients with relevant experience - is becoming well established in health service research in the UK. It is supported by funders and academic institutions. Published principles and guidelines for researchers, developed through consultation and consensus building, are available. Meanwhile, as genome sequencing is adopted into routine health care, translational genomics research and research to evaluate new genomic services are growing. Given the ethical and social implications of offering genome sequencing within a national health service, it is important that researchers give full consideration to planning and implementing meaningful PPI. Here we present five case studies of PPI in a variety of clinical genomic studies, including commentary on positive impacts and suggestions for improvements. We call for funders and academic institutions to continue and increase their efforts to enable and promote PPI across genomic and other health service research.